The experiences of teleradiology end users regarding role extension in a rural district of the North West province: A qualitative analysis - Hafsa Essop; Mable Kekana (AOSIS, 2020)
Background: Teleradiology was implemented across South Africa, to provide reporting services to rural healthcare institutes without a radiologist. This is guided by standard operating procedure manuals (SOP) which standardise the quality of services provided. From observation, end users, namely, the radiographer and referring clinician, experience challenges in fulfilling the roles extending beyond the SOP. Aim: To explore the end users' experiences within this context and the impact it has on service delivery. Setting: A rural district in North West province, South Africa. Method: This was a qualitative, exploratory, descriptive study. Focus group discussions were held with radiographers and referring clinicians from the teleradiology site in the North West province. A one-on-one interview was conducted with a private radiologist at the reporting site in Gauteng. An interview guide was used to ask open-ended questions to address the aim of the study. Results: At the teleradiology site, radiographers and referring clinicians are performing extended roles, not described in the teleradiology service-level agreement (SLA) and felt poorly equipped to fulfil these roles. They also felt that the private radiologists needed training on interprofessional collaboration to understand the challenges facing health professionals at these rural sites. Conclusion: SLA's should align with the clinical needs and practices of the district. This should guide the specific training needs of the end users practicing in rural areas, to support their extended roles in the teleradiology setting. Training should be in-house, ongoing and consistent to cater for the influx of health professionals entering the rural setting using teleradiology systems.